FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PROTOKOL KESEHATAN PENCEGAHAN COVID-19 PADA TENAGA KESEHATAN DI GEDUNG SULAIMAN RUMAH SAKIT ROEMANI - Yugantari, Hidayawati Cahaya; Haikal, Haikal (VISIKES: Jurnal Kesehatan Masyarakat, 2023)
Health workers are an aspect of getting special attention related to serving people who are vulnerable to health problems, especially the transmission of the COVID-19 virus so that they can take care of themselves in terms of implementing health protocols while carrying out their duties. Start the habit of washing hands and using PPE in serving patients to reduce risks at work.The purpose of this study was to analyze factors related to the behavior of the COVID- 19 prevention health protocol in health workers at the Solomon Building, Roemani Hosipital.Data was collected by using a questionnaires to respondents identify knowledge, attitudes, and family support. This study uses a crossectional design with a sample was 67 people who were the total number of nurses and doctors in Solomon's room. Processed by statistical test of rank spearmen.The results of the study, knowledge, attitudes and family support unrelated on the behavior of the COVID-19 health protocol, namely 62 people (95.5%). Unrelated knowledge on the COVID-19 Health Protocol. This is evidenced by the feasible P-Value value of 0.788 >0.05. Attitude unrelated on the COVID-19 Health Protocol. This is evidenced by the PValue worth 0.139 > 0.05. Family Support is not related on the COVID-19 Health Protocol. This is evidenced by the P-Value worth 0.251 > 0.05.Knowledge, attitude and support of health workers in the Solomon building, Roemani Hospital, Semarang is not good. So it is necessary to increase knowledge, attitudes and family support in implementing the COVID-19 health protocol, so that it can achieve the government's goals in reducing the impact of the spread of COVID-19.